The role of business and economic protocol in the ethics of international economic relations - Novik, I. O.; Chyrvon, Anna (Національний технічний університет "Харківський політехнічний інститут", 2023)
This paper extensively explores the pivotal role of business protocol in international economic relations, delving into its historical evolution, contemporary significance, and the challenges it encounters within the dynamic global business environment. The study emphasizes the necessity for nuanced intercultural communication and highlights the adaptability of business protocol to diverse situations. Article discusses the issues of diplomatic and economic protocol and ethics, shedding light on the intricate interplay between international relations and economic activities. Diplomatic protocol, with its established conventions and rituals, plays a crucial role in shaping the discourse between nations, fostering cooperation, and mitigating conflicts. Economic protocol, on the other hand, governs the conduct of nations and businesses in the global marketplace, influencing trade agreements, investment practices, and financial interactions. The examination of these protocols within the framework of ethics becomes imperative as it explores the moral dimensions of diplomatic and economic engagements. Ethical considerations in diplomacy encompass matters of respect, transparency, and adherence to international law, aiming to promote peaceful coexistence and equitable collaboration. Similarly, in the realm of international economics, ethical principles guide decisions regarding resource allocation, corporate responsibility, human rights protection, and the fight against corruption. By delving into the ethical aspects of diplomatic and economic protocols, the article seeks to contribute to a deeper understanding of the values that underpin international interactions. It emphasizes the importance of fostering ethical practices in diplomacy and economic relations, ultimately striving to create a global landscape that values fairness, responsibility, and mutual respect. The current significance of business protocol is underscored in light of its strategic importance in facilitating effective communication and collaboration between nations and businesses. The challenges faced by business protocol in the modern global business arena are thoroughly scrutinized, addressing issues such as cultural diversity, technological advancements, and the need for constant adaptation. In summary, this comprehensive analysis contributes to a nuanced understanding of the multifaceted role of business protocol in international economic relations, shedding light on its historical roots, contemporary significance, and the evolving challenges it faces in the globalized business landscape.

У цьому документі детально досліджується ключова роль бізнес-протоколу в міжнародних економічних відносинах, заглиблюючись у його історичну еволюцію, сучасне значення та виклики, з якими він стикається в динамічному глобальному бізнес-середовищі. Дослідження наголошує на необхідності міжкультурної комунікації з нюансами та підкреслює адаптивність бізнес-протоколу до різноманітних ситуацій. Стаття обговорює питання дипломатичного та економічного протоколу та етики, проливаючи світло на складну взаємодію між міжнародними відносинами та економічною діяльністю. Дипломатичний протокол з його усталеними умовностями та ритуалами відіграє вирішальну роль у формуванні діалогу між націями, розвитку співпраці та пом’якшенні конфліктів. Економічний протокол, з іншого боку, регулює поведінку націй і компаній на глобальному ринку, впливаючи на торговельні угоди, інвестиційну практику та фінансову взаємодію. Вивчення цих протоколів у рамках етики стає обов’язковим, оскільки вони досліджують моральні виміри дипломатичних та економічних зобов’язань. Етичні міркування в дипломатії охоплюють питання поваги, прозорості та дотримання міжнародного права, спрямовані на сприяння мирному співіснуванню та рівноправній співпраці. Подібним чином у сфері міжнародної економіки етичні принципи керують рішеннями щодо розподілу ресурсів, корпоративної відповідальності, захисту прав людини та боротьби з корупцією. Заглиблюючись в етичні аспекти дипломатичних та економічних протоколів, стаття прагне зробити внесок у глибше розуміння цінностей, які лежать в основі міжнародної взаємодії. Він підкреслює важливість сприяння етичним практикам у дипломатії та економічних відносинах, зрештою, прагнучи створити глобальний ландшафт, який цінує справедливість, відповідальність і взаємну повагу. Сучасне значення бізнес-протоколу підкреслюється в світлі його стратегічної важливості для сприяння ефективній комунікації та співпраці між країнами та бізнесом. Виклики, з якими стикається бізнес-протокол на сучасній глобальній бізнес-арені, ретельно досліджуються, розглядаючи такі питання, як культурне розмаїття, технологічний прогрес і потреба в постійній адаптації. Таким чином, цей всебічний аналіз сприяє тонкому розумінню багатогранної ролі бізнес-протоколу в міжнародних економічних відносинах, проливаючи світло на його історичне коріння, сучасне значення та нові виклики, з якими він стикається в глобалізованому бізнес-ландшафті.
Роль ділового та економічного протоколу в етиці міжнародних економічних відносин
Keywords: business protocol; international relations; intercultural communication; diplomatic protocol; partnership establishment; economic development; діловий протокол; міжнародні відносини; міжкультурна комунікація; дипломатичний протокол; встановлення партнерства; економічний розвиток